(untitled) (Kinesiology, 2019)
The purpose of this research was to investigate the effects of a physical training program and semester break periods on chosen physical abilities and basic body composition indicators among police trainees. Body weight (BW), waist circumference (WC), push-ups (PU), sit-ups (SU) and 2.4 km run (RUN) times of 420 male trainees attending the Abu Dhabi Police College were collected. The testing was conducted by the police education centre during routine testing periods (June, September, December, May) which bracketed the semesters and could be used to investigate the impacts of the physical training program and any potential detraining occurring over the semester break. A repeated measure analysis of variance was performed to identify changes in results across the time periods with a Bonferroni post-hoc adjustment to identify where differences, if any, lay. The level of significance was set at 0.05 a priori. Following the semester break period from June to September BW, WC and RUN increased significantly (p<0.01), while PU and SU decreased significantly (p<0.01). WC and RUN significantly decreased from September to December and December to May (p<0.01); BW significantly decreased September to December (p<0.01), but did not change from December to May (p=0.267); PU and SU significantly increased from September to December (p<0.01) and December to May (p=0.018 and p<0.01).